Back Cover: Efficient Electrosynthesis of AgIISO4: A Powerful Oxidizer and Narrow Band Gap Semiconductor (Eur. J. Inorg. Chem. 35/2016). Issue 35 (December 2016) - Połczyński, Piotr; Gilewski, Tomasz E.; Gawraczyński, Jakub; Derzsi, Mariana; Leszczyński, Piotr Jerzy; Gadomski, Wojciech; Mazej, Zoran; Jurczakowski, Rafał; Grochala, Wojciech
Abstract : The back cover picture shows the formation of black crystallites of Ag II SO4 on a fluorine‐doped tin oxide electrode by electrosynthesis during the electrolysis of Ag I 2 SO4 solution in sulfuric acid. The so‐formed compound shows excellent crystallinity, as compared to that obtained by a chemical route, and it has a narrow band gap of 1.0 eV, which is of interest for photoelectrochemical applications. Details are discussed in the Communication by R. Jurczakowski, W. Grochala et al. onp. 5401 ff .